2009
DOI: 10.1538/expanim.58.85
|View full text |Cite
|
Sign up to set email alerts
|

The Mouse Resources at the RIKEN BioResource Center

Abstract: Abstract:Mice are one of the most important model organisms for studying biological phenomena and diseases processes in life sciences. The biomedical research community has succeeded in launching large scale strategic knockout mouse projects around the world. RIKEN BRC, a comprehensive government funded biological resource center was established in 2001. RIKEN BRC has been acting as the core facility for the mouse resources of the National BioResource Project (NBRP) of the Ministry of Education, Culture, Sport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…It was therefore argued that domesticated inbred mice are, in many ways, poorly suited to serve as models of 'normal' mice. Furthermore, it was suggested that genetically modifiable strains derived from wild house mice might serve as useful models, especially for experimental work in behavioural and brain sciences 30 . Thus, findings obtained from studies in wild-derived stocks might provide valuable opportunities to unravel the relationships between genotype and complex natural phenotypic traits that are reduced or even absent in domesticated stocks 10,14 , for example agonist behaviours in males and females, resistance to capture by humans (reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…It was therefore argued that domesticated inbred mice are, in many ways, poorly suited to serve as models of 'normal' mice. Furthermore, it was suggested that genetically modifiable strains derived from wild house mice might serve as useful models, especially for experimental work in behavioural and brain sciences 30 . Thus, findings obtained from studies in wild-derived stocks might provide valuable opportunities to unravel the relationships between genotype and complex natural phenotypic traits that are reduced or even absent in domesticated stocks 10,14 , for example agonist behaviours in males and females, resistance to capture by humans (reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the work of EMMA plays a crucial role in exploiting the tremendous potential benefits to human health presented by the current research in mammalian genetics (59). In Asia, AMMRA (Asian Mouse Mutagenesis Resources Association) was organized and shared their mice resources and information (60).…”
Section: Archiving and Bankingmentioning
confidence: 99%
“…It always plays a key role in functional genomics [34]. Use of the BAC clone is not limited to the investigation of SNP.…”
Section: Bac Clonesmentioning
confidence: 99%